ANALISIS YURIDIS PENGATURAN PEMISAHAN BERKAS PERKARA (SPLITSING) BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Annisa, Fitri; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
In the case of the settlement of criminal cases there are arrangements that do not provide legal certainty that leads to multiple interpretations leading to misappropriation. In the case of the formulation of a criminal case becomes one of confusion among law enforcers in particular the separation of the file of the case or Splitsing. Separation of a case file or Splitsing is regulated in Article 142 of the Criminal Procedure Code, namely